Velocidade da marcha como preditora de quedas em idosos com transtorno neurocognitivo leve e doença de Alzheimer - Masse, Fernando Arturo Arriagada (Universidade Federal de São Carlos, 2017)
Background: Little is known about how the change in walking speed in longitudinal studies can predict the occurrence of falls in older adults with mild cognitive impairment. Objetives: To identify if there are differences in the gait speed of Cognitively Preserved (CPr) elderly persons, elderly persons with Mild Cognitive Impairment (MCI) and with Alzheimer`s Disease (AD) in mild stage, in a 6-month period. To verify if the change in the gait speed (ΔGS= Final Gait speed – Initial Gait speed) predicts the occurrence of falls in elderly with MCI and AD in mild stage. Methods: 110 elderly people participated in the study. Out of these: 40 with CPr, 36 with MCI and 34 with AD in the mild stage. Initially the 10-meter walk test was applied and a fall schedule was given. A 6-month follow-up was carried out, by means of monthly telephone calls to the volunteers and the filling of a fall schedule. After six months, the 10-meter walk test was applied and the fall schedule was retrieved. Results: The MCI and AD groups of elderly in mild stage presented lower gait speed compared to the elderly in the CPr group at the two assessment moments. There was no significant difference in delta gait speed amongst the groups. In the age-adjusted univariate logistic regression analysis, the delta failed to predict falls in the elderly with MCI or in elderly with AD. Conclusion: Older adults with MCI and AD in the mild stage were identified as having lower gait speed compared to CPr sujeitos. Changing in the gait speed over a six-month period does not predict the occurrence of falls in elderly with MCI or AD in mild stage.
Keywords: Velocidade da marcha; Doença de Alzheimer; Comprometimento cognitivo leve; Quedas; Gait speed; Alzheimer disease; Mild cognitive impairment; Falls; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL